KEPEMIMPINAN SPIRITUAL DI PERPUSTAKAAN UNTUK MENGHADAPI ERA SOCIETY 5.0 - Rika Fatayat (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2021)
This study aims to describe spiritual leadership that can be applied in libraries to face the era of society 5.0. The results of this study indicate that social change towards the era of society 5.0 requires a leadership perspective that prioritizes innovation, motivation, human resource capabilities, and human relations. The leader is a factor that determines the success of the organization in achieving the goals that have been set. In the era of society 5.0, a good leadership pattern in the library is very much needed. In the context of the library, the concept of spiritual leadership will inspire and motivate human resources in achieving the vision and goals of the organization which in turn can produce superior human resources who have optimal abilities in carrying out library services productively. The pattern of spiritual leadership that combines vision, hope/belief and altruistic love can be a leadership choice that can be applied in the library.